Implementation of the Literacy Movement Program in Increasing Reading Interest Among 4th Grade (B) Students at SDN 7 Sambik Bangkol, North Lombok Regency, Academic Year 2024/2025 - Khaeratul, Riza; Jannah, Rauhun; Ihwan, Ihwan (Peneliti.net, 2025)
This study aims to identify, describe, and explore data regarding the implementation of the School Literacy Movement (GLS) program in increasing reading interest among fourth-grade students at SDN 7 Sambik Bangkol, Gangga District, North Lombok Regency, for the 2024/2025 academic year. This study was conducted at SDN 7 Sambik Bangkol, Gangga District. It employed a descriptive qualitative method. Data collection was carried out using observation, interviews, and documentation. Following data collection, the researcher proceeded with data reduction, data presentation, and conclusion drawing. The validity of the data was then tested using source triangulation, technique triangulation, and time triangulation. The results of the study showed that the implementation of the GLS program included 15 minutes of reading before starting lessons, the provision of reading corners in classrooms, and the involvement of parents in accompanying students to read at home. This program was able to increase students' interest in reading, as seen from their enthusiasm in reading activities and the frequency of visits to the school library. The obstacles faced were the absence of a library, some students still unable to understand what they read, lack of attention or guidance for students at home, so that literacy could only be carried out at school while at home students did not do it, and students lacked focus due to the influence of their environment.